2021
DOI: 10.1088/1748-0221/16/03/p03045
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent PIC simulations of ultimate space charge compensation with electron lenses

Abstract: Further progress of fundamental particle physics requires high intensity and high brightness of accelerated proton and ion beams. This goal is essential for the FAIR hadron beams at GSI, for the neutrino production at the facilities such as Fermilab and JPARC, and for the Large Hadron Collider luminosity at CERN. One of the most formidable obstacles toward that goal is the beam's own space charge, whose forces cause beam emittance growth, losses and lifetime degradation. Typically, such effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In this regime, the measured beam potential was 10-30 V, compared to the 200 V measured without residual gas injection. The achieved number of stored protons ranged from 0.75×10 12 to 1.25×10 12 , depending on gas species, almost an order of magnitude increase from the uncompensated case. When an accelerating voltage was applied to the beam to compensate energy loss, the lifetime and number of stored protons increased.…”
Section: Jinst 16 P03048mentioning
confidence: 96%
See 1 more Smart Citation
“…In this regime, the measured beam potential was 10-30 V, compared to the 200 V measured without residual gas injection. The achieved number of stored protons ranged from 0.75×10 12 to 1.25×10 12 , depending on gas species, almost an order of magnitude increase from the uncompensated case. When an accelerating voltage was applied to the beam to compensate energy loss, the lifetime and number of stored protons increased.…”
Section: Jinst 16 P03048mentioning
confidence: 96%
“…For more information on ELs for SCC, see also refs. [11,12]. Although SCC using an EC has not been fully implemented in circular machines, there have been several experimental and computational efforts to study SCC in a ring, showing promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Space-charge neutralization and compensation are routinely used in one-pass systems, such as beam lines for low-energy beam transport (LEBT) and rf photoinjectors. In rings, SCC with electrons offers several advantages [32] and could enable higher intensities and brightnesses by reducing losses and emittance growth [51,[53][54][55][56][57][58][59][60]. Proof-of-principle experiments are needed to understand the limits of the method and to explore the stability of the system.…”
Section: Space-charge Compensationmentioning
confidence: 99%
“…To reduce these detrimental effects, it was suggested to use electron lenses to compensate the space-charge forces [53]. Further analysis and computer modeling [51,54,[58][59][60] indicated that compensation with electron lenses may enable an accelerator to exceed the space-charge limit and to operate with much larger tune-shift parameters, up to −1.0. The SCC e-lens should have a transverse currentdensity profile close to that of the proton beam.…”
Section: Space-charge-compensating Electron Lensmentioning
confidence: 99%
See 1 more Smart Citation